Pengaruh Pengaturan Kerja Fleksibel dan Lingkungan Kerja Terhadap Kepuasan Kerja pada Kantor Pusat Direktorat Jenderal Bea dan Cukai - Aidina, Salsabilla Fahira; Parimita , Widya; Faslah, Roni (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to: 1) Examine flexible work arrangements, the work environment, and job satisfaction at the Headquarters of the Directorate General of Customs and Excise. 2) Determine the effect of flexible work arrangements on job satisfaction at the Headquarters of the Directorate General of Customs and Excise. 3) Determine the effect of the work environment on job satisfaction at the Headquarters of the Directorate General of Customs and Excise. 4) Determine the combined effect of flexible work arrangements and the work environment on job satisfaction at the Headquarters of the Directorate General of Customs and Excise. The study surveyed 120 employees at the Headquarters of the Directorate General of Customs and Excise using a questionnaire-based survey method, simple random sampling, and analysis via SPSS version 24. Multiple linear regression analysis was employed to analyze the data. The results indicate a positive and significant influence of flexible work arrangements and the work environment on job satisfaction. Both flexible work arrangements and the work environment affect employee job satisfaction; the t-statistic for flexible work arrangements regarding job satisfaction was 7.265 (> 1.65) with a significance value of 0.000 (< 0.005), while the t-statistic for the work environment regarding job satisfaction was 11.339 (> 1.65) with a significance value of 0.000 (< 0.005). Flexible work arrangements and the work environment simultaneously influenced job satisfaction, with an F-statistic of 705.3 (> 3.07) and a significance value of 0.000.